A glass-ceramic and a method for its production and use
Patent Information
- Application Number
- CN202611053547.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-15
- Publication Date
- 2026-10-30
AI Technical Summary
[0005]但是玻璃陶瓷的稳定性和发光性能仍有进一步优化的空间
由于Eu和Ba的原子半径接近,因此形成玻璃陶瓷析出的微晶中,Eu会部分取代Ba的晶格位点。本发明通过优化玻璃陶瓷的组分,显著提高了其稳定性和发光性能。所述玻璃陶瓷材料在420K时仍保持300K发光强度的90.37%,热稳定性优异;所述玻璃陶瓷的量子效率达到74%,即具有优异的发光性能;该玻璃陶瓷的光谱范围为375~750nm,可作为蓝色荧光材料开发应用于激光照明中,也可以通过补充红光部分,可以应用于植物照明领域;推动新型发光材料在植物照明领域的广泛应用,为现代农业设施的发展提供强有力的技术支持,助力农业生产实现高效、绿色和可持续发展。
Smart Images

Figure CN123003148A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of luminescent materials technology, and in particular to a glass ceramic, its preparation method, and its application. Background Technology
[0002] Currently, solid-state lighting is widely used due to its comprehensive advantages such as energy saving, environmental protection, compactness, and long lifespan. Solid-state lighting refers to the technology of using solid-state electronic components as excitation sources, represented by light-emitting diodes (LEDs) and laser diodes (LDs). Due to limitations in the excitation characteristics of semiconductors and lasers, it is impossible to obtain a continuous white light spectrum solely relying on solid-state electronic components. To obtain a continuous white light spectrum, it is usually necessary to couple the luminescent material with an LED / LD chip to obtain a white light lighting device. For example, commercially available white LED (WLED) and LD lighting devices consist of a blue LED / LD chip and a yellow YAG:Ce 3+ Composed of phosphors.
[0003] For high-power lighting, the heat generated by energy loss (such as photoelectric energy conversion and Stokes shift of luminescent materials) increases dramatically. Reports indicate that the cumulative heat generated by high-power LED chips during operation can exceed 200°C, and under 10W blue LED irradiation, the internal temperature of the LD device can reach 260°C within 10 minutes. Under such prolonged high-temperature irradiation, phosphors will face problems such as thermal quenching and decreased luminous efficiency, inevitably leading to serious issues like color drift and reduced luminous efficiency. Furthermore, irradiation of high-power chips will inevitably accelerate the aging and yellowing of heat-sensitive organic binders such as resins or silicone resins, and may even cause ablation. Therefore, heat dissipation has become one of the main bottlenecks restricting the development of high-power solid-state lighting, posing a severe challenge to exploring luminescent materials with high luminous efficiency and excellent thermal stability based on existing LED / LD chip technology.
[0004] Therefore, more and more scientists are focusing on solid-state luminescent materials with excellent optical properties. Solid-state luminescent materials mainly include single crystals, ceramics, and glasses. Single crystals and ceramics are limited in market application due to their high manufacturing costs and inability to be mass-produced. Glass, due to its amorphous structure, suffers from low luminous efficiency. However, by controlling the crystallization of a base glass with specific components during heating, glass-ceramics (glass-ceramics, where the microcrystalline phase is distributed within the glass phase) containing a large number of microcrystalline and glassy phases can be produced. Glass-ceramics are a class of advanced optical functional materials, where the crystallization of the precursor glass is precisely controlled through a customized heat treatment scheme. Unlike traditional amorphous glasses or completely dense polycrystalline ceramics, glass-ceramics exhibit a unique hybrid microstructure, characterized by one or more optically functional crystalline phases uniformly dispersed within the residual glass matrix. This microstructure bridges the gap between optical glass and ceramics, effectively combining the optical transparency of glass with the mechanical stability / optical functionality of ceramics, achieving synergistic performance enhancement. The main advantage of glass-ceramics lies in the adjustability of its structure achieved through compositional design and optimized heat treatment. By adjusting parameters such as heating rate, temperature distribution, and duration, researchers can precisely control the crystal phase size (from nanometers to micrometers), morphology (e.g., spherical, rod-shaped, or dendritic structures), volume fraction (up to ~100%), and spatial distribution, all of which directly affect light scattering, absorption, and emission properties. This microstructure control, combined with the synergistic effect between the crystalline and glass phases, enhances overall performance by integrating the advantages of both components. For example, the glass matrix provides optical transparency (80% visible light transmittance), chemical durability (acid / alkali resistance), and ease of shaping (through melting / forming techniques). The crystalline phase offers higher luminous efficiency by suppressing non-radiative recombination pathways within an ordered crystalline environment. Rare-earth-doped fluorescent glass-ceramics combine the advantages of phosphor crystals and glass, possessing high luminous efficiency and excellent thermal stability, along with characteristics such as hardness, density, uniformity, flexible composition control, corrosion resistance, ease of processing and shaping, low cost, mass production capability, and a viscous network structure that ensures uniform crystal dispersion. Therefore, glass-ceramics possess these unique advantages, making them suitable for the high-power solid-state lighting market.
[0005] However, there is still room for further optimization of the stability and luminescence properties of glass ceramics. Summary of the Invention
[0006] This invention aims to at least solve one of the technical problems existing in the prior art. To this end, this invention proposes a glass-ceramic that can effectively improve optical properties and radiative luminescence intensity.
[0007] The present invention also provides a method for preparing the above-mentioned glass ceramic.
[0008] The present invention also provides applications of the aforementioned glass ceramics.
[0009] According to an embodiment of a first aspect of the present invention, a glass-ceramic is provided, the glass-ceramic comprising the chemical formula BaMg2Al6Si9O 30 :xEu 2+ The crystal phase structure; and the value of x ranges from 0.1 to 0.9%.
[0010] Where x represents the molar percentage of europium ions in the europium source among all the raw materials used in the preparation of the glass ceramic.
[0011] The glass-ceramic according to embodiments of the present invention has at least the following beneficial effects: Because Eu and Ba have similar atomic radii, Eu partially replaces Ba lattice sites in the microcrystals precipitated in the glass-ceramic. This invention significantly improves the stability and luminescence performance of the glass-ceramic by optimizing its composition. The glass-ceramic material retains 90.37% of its luminescence intensity at 300K at 420K, demonstrating excellent thermal stability. The glass-ceramic achieves a quantum efficiency of 74%, indicating excellent luminescence performance. With a spectral range of 375–750 nm, this glass-ceramic can be developed as a blue fluorescent material for laser lighting, and by supplementing the red light portion, it can be applied to plant lighting. This promotes the widespread application of novel luminescent materials in plant lighting, provides strong technical support for the development of modern agricultural facilities, and helps agricultural production achieve efficient, green, and sustainable development.
[0012] According to some embodiments of the present invention, BaMg2Al6Si9O 30 :xEu 2+ The value of x in the equation ranges from 0.1 to 0.9%; for example, it can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%; or any range of values formed by any two of the above points.
[0013] According to some embodiments of the present invention, the glass-ceramic exhibits photoluminescence.
[0014] According to some embodiments of the present invention, the excitation spectrum of the glass-ceramic is in the range of 230~440nm.
[0015] According to some embodiments of the present invention, the peak value of the excitation spectrum of the glass ceramic is between 300 and 340 nm. For example, it can be 300 nm, 305 nm, 310 nm, 315 nm, 320 nm, 325 nm, 330 nm, 335 nm, or 340 nm; or the peak value is within the range formed by any two of the above values.
[0016] According to some embodiments of the present invention, the emission spectrum peak of the glass-ceramic is in the range of 445~470nm. For example, it can be 445nm, 450nm, 455nm, 460nm, 465nm, or 470nm; or the peak value is between any two of the above values.
[0017] According to some embodiments of the present invention, the photoluminescence quantum efficiency of the glass-ceramic is ≥43%. For example, it can be 43%, 45%, 50%, 55%, 60%, 65%, 70%, 72%, 75%; or a range of values consisting of any two of the above points.
[0018] According to some embodiments of the present invention, the ratio of the luminous intensity of the glass-ceramic at 420K and 300K is ≥90%. For example, it can be 90%, 90.5%, 91%; or a range of values consisting of any two of the above points.
[0019] According to some embodiments of the present invention, the ratio of the luminous intensity of the glass-ceramic at 570K and 300K is ≥75%. For example, it can be 75%, 75.5%, 76%; or a range of values consisting of any two of the above points.
[0020] According to an embodiment of a second aspect of the present invention, a method for preparing the glass-ceramic is provided, the method comprising the following steps: S1. Mix magnesium source, aluminum source, silicon source, barium source and europium source, and melt and cool the resulting mixture in a reducing atmosphere; S2. The product obtained in step S1 is subjected to heat treatment in a reducing atmosphere; the temperature of the heat treatment is >950℃ and <1000℃.
[0021] Since the preparation method employs all the technical solutions of the glass-ceramics described in the above embodiments, it possesses at least all the beneficial effects brought about by the technical solutions of the above embodiments. Furthermore, In step S2, the temperature limit of the heat treatment and the glass-ceramic raw material work together to further improve the thermal stability and luminescence performance of the obtained glass-ceramic. Moreover, the preparation method is carried out under normal pressure, and the preparation process is simple, low-cost, non-toxic and pollution-free, and can be mass-produced, making the glass-ceramic a promising candidate for application in the field of display lighting as a new type of optical functional solid material.
[0022] According to some embodiments of the present invention, in step S1, the mixture comprises, by mole percentage: Magnesium source 18% ± 0.1%; Aluminum source 22% ± 0.1%; Silicon source 55% ± 0.1%; Barium source 5%±0.1%-x / 2; Europium source x / 2.
[0023] Regarding the molar percentage of raw materials other than barium and europium sources, it should be noted that: In component design, the components only need to fall within the crystalline region of the target crystalline phase; strict adherence to stoichiometry is not required. During crystallization, atoms undergo a certain degree of migration, leading to elemental segregation. Elements conforming to the chemical formula ratio accumulate in the crystalline region. Characterization of the phase and structure confirms that the component can successfully synthesize the glass-ceramic of the target crystalline phase. Furthermore, reducing the aluminum content in the component lowers the melting point of the aluminosilicate glass-ceramic, thus reducing the requirements for its preparation conditions.
[0024] It should be further noted that 1 mol of europium source typically contains 2 mol of europium ions, thus limiting the amount of europium source to x / 2. Furthermore, since europium ions occupy the lattice sites of barium ions, the sum of the molar percentages of europium source and barium source is fixed.
[0025] According to some embodiments of the present invention, in step S1, the magnesium source includes magnesium oxide.
[0026] According to some embodiments of the present invention, in step S1, the aluminum source includes aluminum oxide.
[0027] According to some embodiments of the present invention, in step S1, the silicon source includes silicon oxide.
[0028] According to some embodiments of the present invention, in step S1, the barium source includes at least one of barium oxide (barium oxide) and barium carbonate (barium carbonate). Barium carbonate is preferred.
[0029] According to some embodiments of the present invention, in step S1, the europium source includes europium trioxide (Eu2O3).
[0030] According to some embodiments of the present invention, in step S1, the composition of the magnesium source, aluminum source, silicon source, barium source and europium source, in molar percentage, is as follows: MgO 18%; Al2O3 22%; SiO2 55%; BaCO3 4.55%~4.95%; Eu2O3 0.05%~0.45%.
[0031] Under the above component ratio, the resulting glass ceramic has superior optical properties.
[0032] According to some embodiments of the present invention, in step S1, the mixing is a grinding mixture.
[0033] According to some embodiments of the present invention, the grinding and mixing time is 20 to 30 minutes. For example, it can be 20 minutes, 22 minutes, 24 minutes, 25 minutes, 26 minutes, 28 minutes, or 30 minutes; or a range of values composed of any two of the above points.
[0034] According to some embodiments of the present invention, in step S1, the melting temperature is 1400~1500℃. For example, it can specifically be 1400℃, 1450℃, 1500℃; or a range of values composed of any two of the above points.
[0035] According to some embodiments of the present invention, in step S1, the melting time is 3-4 hours. Specifically, it can be 3 hours, 3.5 hours, or 4 hours; or a range of values consisting of any two of the above points. In actual production, after complete melting, the glass is removed as soon as possible and rapidly cooled to avoid crystallization, thereby obtaining amorphous glass as a precursor. The rapid cooling method includes natural cooling in air without applying any additional cooling measures.
[0036] According to some embodiments of the present invention, in step S2, the temperature of the heat treatment is 960~1000℃. For example, it can specifically be 960℃, 970℃, 980℃, 990℃, 1000℃; or a range of values composed of any two of the above points.
[0037] According to some embodiments of the present invention, in step S2, the duration of the heat treatment is 6h to 11h. For example, it can be 6h, 7h, 8h, 9h, 10h, or 11h; or a range of values composed of any two of the above points.
[0038] According to some embodiments of the present invention, in step S1 and / or step S2, the reducing atmosphere is independently provided by at least one of carbon powder and hydrogen.
[0039] According to an embodiment of the third aspect of the present invention, a glass ceramic as described in the first aspect of the present invention, or a glass ceramic prepared by the preparation method described in the second aspect of the present invention, is provided for use in the lighting field.
[0040] Since the application adopts all the technical solutions of the glass ceramics or preparation methods of the above embodiments, it has at least all the beneficial effects brought about by the technical solutions of the above embodiments.
[0041] According to some embodiments of the present invention, the lighting field includes at least one of plant lighting and laser lighting.
[0042] According to some embodiments of the present invention, the application in the field of plant lighting includes plant lighting devices, which include the glass ceramic.
[0043] Other features and advantages of the invention will be set forth in the description which follows, and will be apparent in part from the description, or may be learned by practicing the invention. Attached Figure Description
[0044] Figure 1 These are the XRD patterns of the glass ceramics obtained in Examples 1-5 of this invention; Figure 2 This is the normalized emission and excitation spectrum of the glass-ceramic obtained in Example 1 of the present invention; Figure 3 This is the normalized emission and excitation spectrum of the glass-ceramic obtained in Example 2 of the present invention; Figure 4 These are appearance images of the precursor glass and glass-ceramic obtained in Embodiment 2 of the present invention before and after ultraviolet light excitation; Figure 5 These are the emission spectra of the glass ceramics obtained in Examples 1-5 of this invention; Figure 6 This is the XRF elemental analysis spectrum of the glass-ceramic obtained in Example 2 of the present invention; Figure 7 These are TEM images of the precursor glass (left) and glass-ceramic (right) obtained in Embodiment 2 of the present invention; Figure 8 These are the quantum efficiency (PLQY) graphs of the glass ceramics obtained in Examples 1-5 of this invention; Figure 9 This is the temperature-varying spectrum of the glass-ceramic obtained in Example 2 of the present invention; Figure 10 This is a temperature-varying dot plot of the glass-ceramic obtained in Embodiment 2 of the present invention; Figure 11 This is the emission spectrum of the glass-ceramic obtained in Example 2 of the present invention during the 0-30 day period of water stability. Figure 12 This is a spectral diagram of the glass-ceramic plant lighting device obtained in Embodiment 2 of the present invention; Figure 13 This is the normalized emission and excitation spectrum of the glass-ceramic obtained in Example 3 of the present invention; Figure 14 This is the normalized emission and excitation spectrum of the glass-ceramic obtained in Example 4 of the present invention; Figure 15 This is the normalized emission and excitation spectrum of the glass-ceramic obtained in Example 5 of the present invention. Detailed Implementation
[0045] To better illustrate the purpose, technical solution, and advantages of this invention, the invention will be further described below with reference to specific embodiments and comparative examples. The purpose of this description is to provide a detailed understanding of the invention, not to limit its scope. All other embodiments obtained by those skilled in the art without inventive effort are within the protection scope of this invention.
[0046] Example 1 This example demonstrates the preparation of a glass-ceramic with the chemical formula BaMg2Al6Si9O. 30 :xEu 2+ x = 0.1%; The specific steps of the preparation method are as follows: S1. Mix the magnesium source MgO, aluminum source Al2O3, silicon source SiO2, barium source BaCO3, and europium source Eu2O3 in an agate mortar and grind for 30 minutes to obtain a mixed powder, and then put it into a corundum crucible. The crucible containing the mixed powder was placed in a large covered crucible filled with activated carbon (which generates CO during heating and provides a reducing atmosphere). The crucible was kept at 1500℃ for 3 hours in a box furnace to melt it. After the holding time was completed, the crucible was immediately removed and rapidly cooled (it was placed in the air to cool naturally; the cooling rate was measured to be about 30℃ / min) to obtain the precursor amorphous glass. S2. The precursor amorphous glass obtained in step S1 is heat-treated in a system containing activated carbon at a temperature of 970°C. After 11 hours of heat treatment, the glass-ceramic sample crystallizes uniformly to obtain the glass-ceramic with the target chemical formula.
[0047] Example 2 This example demonstrates the preparation of a glass-ceramic with the chemical formula BaMg2Al6Si9O. 30 :xEu 2+ x=0.3%; The difference between the preparation method and Example 1 is: The raw material ratios are different. In this example, the raw material ratios are based on the molar percentages of 18%MgO-22%Al2O3-55%SiO2-4.85%BaCO3-0.15%Eu2O3.
[0048] Example 3 This example demonstrates the preparation of a glass-ceramic with the chemical formula BaMg2Al6Si9O. 30 :xEu 2+ x=0.5%; The difference between the preparation method and Example 1 is: The raw material ratios are different. In this example, the raw material ratios are based on the molar percentages of 18%MgO-22%Al2O3-55%SiO2-4.75%BaCO3-0.25%Eu2O3.
[0049] Example 4 This example demonstrates the preparation of a glass-ceramic with the chemical formula BaMg2Al6Si9O. 30 :xEu 2+ x=0.7%; The difference between the preparation method and Example 1 is: The raw material ratios are different. In this example, the raw material ratios are based on the molar percentages of 18%MgO-22%Al2O3-55%SiO2-4.65%BaCO3-0.35%Eu2O3.
[0050] Example 5 This example demonstrates the preparation of a glass-ceramic with the chemical formula BaMg2Al6Si9O. 30 :xEu 2+ x=0.9%; The difference between the preparation method and Example 1 is: The raw material ratios are different. In this example, the raw material ratios are based on the molar percentages of 18%MgO-22%Al2O3-55%SiO2-4.55%BaCO3-0.45%Eu2O3.
[0051] Comparative Example 1 This example aims to prepare a glass-ceramic with the chemical formula BaMg2Al6Si9O. 30 :xEu 2+ x=0.3%; The difference between the preparation method and Example 2 is: In step S2, the heat treatment temperature is 900℃.
[0052] Comparative Example 2 This example aims to prepare a glass-ceramic with the chemical formula BaMg2Al6Si9O. 30 :xEu 2+ x=0.3%; The difference between the preparation method and Example 2 is: In step S2, the heat treatment temperature is 1100℃ and the time is 3 hours.
[0053] Application examples This example provides a device for plant lighting, specifically using the glass-ceramic and red light emitting material (commercially available CaAlSiN3:Eu) obtained in the embodiment. 2+ It is prepared using [a specific ingredient] as raw material. Specifically: The thin film prepared by the glass-ceramic obtained in the examples or comparative examples and red phosphor (the phosphor and PDMS (20% ratio) were uniformly mixed and then cured) was encapsulated. The thickness ratio of glass-ceramic to thin film was approximately 3:1.
[0054] Test case The first aspect of this example tested the XRD patterns of the glass-ceramics obtained in the examples and comparative examples; the results showed that the XRD diffraction peaks of the glass-ceramic material obtained in Example 1 were consistent with those of the standard card PDF#83-0740 (BaMg2Al6Si9O). 30 The one-to-one correspondence indicates that the glass-ceramic material with the target chemical formula was successfully prepared; however, in Comparative Example 1, the heat treatment temperature in step S2 was too low, and only an amorphous glass material could be obtained (an amorphous spectrum was obtained by XRD testing); in Comparative Example 2, the heat treatment temperature in step S2 was too high, resulting in glass softening. Softening leads to appearance deformation, uncontrolled crystallization, and the formation of impurity phases, thus also preventing the formation of glass-ceramic material. The XRD test results of the glass-ceramics obtained in the examples are as follows: Figure 1 As shown.
[0055] The second aspect of this example analyzes the elemental distribution of the glass-ceramics obtained in the embodiments. One of the testing methods is elemental analysis of the glass-ceramics using XRF, which shows that Ba, Mg, Al, Si, O, and Eu are uniformly distributed in the glass-ceramics; the test results of the sample obtained in Example 2 are as follows. Figure 6 As shown. The second test method, TEM testing, shows that no obvious diffraction rings were observed in the TEM image of the precursor glass obtained in step S1, confirming the amorphous nature of the precursor glass; while clear and orderly arranged diffraction spots were observed in the glass-ceramic sample, which is a characteristic of the long-range order of crystals; the TEM results of the intermediate and final products in Example 2 are shown below. Figure 7 As shown, the left side represents the precursor, and the right side represents the resulting glass-ceramic product. The results of all embodiments are comparable to those of Embodiment 2; XRF and TEM test images confirm that the glass-ceramic samples were successfully prepared in the embodiments.
[0056] The third aspect of this example tested the photoluminescence properties of the glass-ceramic obtained in the example at room temperature (300K); specifically, when excited by 365nm wavelength violet light (the quantum conversion rate was almost the same under different light intensities), the glass-ceramic exhibited bright blue emission. Its normalized excitation and emission spectra at room temperature were measured using an Edinburgh FS980 fluorescence spectrometer; the emission spectrum showed the presence of Eu. 2+ 4f of ions 6 5d 1 -4f 7The transition is a typical broad-peak emission, with a center wavelength in the range of 445-470 nm; the excitation spectrum covers a wide band of 230 nm-440 nm, and the excitation peak is distributed between 300-340 nm. With increasing Eu doping concentration, the center wavelength of the emission spectrum redshifts, and both the intensity of the emission spectrum and the quantum efficiency of the glass-ceramic show a trend of first increasing and then decreasing; compared with the precursor obtained in step S1, the luminescence intensity of the glass-ceramic obtained in step S2 is significantly improved. The peak values of the excitation and emission spectra of the glass-ceramic obtained in the examples are shown in Table 1; the specifically fitted excitation and emission spectra are shown in... Figures 2-3 As shown in 5, 13-15, the quantum efficiency results are compared to, for example... Figure 8 As shown; Comparison of the appearance of the glass-ceramic obtained in Example 2 before and after excitation. Figure 4 As shown, glass represents the product obtained in step S1 of Example 2.
[0057] Table 1. Excitation and emission peak values of the glass-ceramics obtained in the examples. project Excite nm emit nm Example 1 329 449 Example 2 305 450 Example 3 337 456 Example 4 328 466 Example 5 335 469 The fourth aspect of this example tested the thermal stability of the glass ceramic obtained in Example 2. The test method was variable-temperature spectroscopy, specifically, the emission spectrum of the glass ceramic was tested at different temperatures when the excitation light was a fixed intensity 365nm incident light. The thermal stability was then visually analyzed using variable-temperature spectral graphs and intensity line graphs. The results showed that the glass ceramic sample obtained in Example 2 maintained 90.37% of its room temperature (300K) intensity at 420K. Even at a high temperature of 570K, no thermal quenching occurred; instead, it maintained 75.35% of its room temperature intensity. The thermal stability performance of the products obtained from different examples was comparable. This sufficiently demonstrates that the glass ceramic sample has excellent thermal stability, giving it a strong competitive advantage in the field of solid-state lighting. The emission spectra and intensities of the glass ceramic obtained in Example 2 at different temperatures are shown below. Figures 9-10 As shown.
[0058] The fifth aspect of this example tested the water resistance of the glass-ceramic sample obtained in Example 2, specifically by placing it in water for 30 days and measuring its emission spectral intensity; the results showed that the intensity did not change; this is because the rigid glass network structure holds BaMg2Al6Si9O 30 The crystal encapsulation gives it excellent water stability. Specific water resistance test results are as follows: Figure 11 As shown, these spectral data and various stability tests are sufficient to demonstrate that the glass-ceramic sample possesses excellent optical properties, giving it a direct competitive advantage in device applications.
[0059] The sixth aspect of this example tested the emission spectrum of the plant lighting device obtained in the application example (using the glass-ceramic obtained in Example 2 as the raw material), and the results are as follows: Figure 12As shown in the figure, BMASO:Eu 2+ This refers to the glass-ceramic obtained in Example 2; CASN is CaAlSiN3:Eu. 2+ Red phosphor. Because plants selectively absorb light waves, they do not absorb certain wavelengths, such as green light around 550nm. The light sources absorbed by plants during photosynthesis mainly include the blue light band (400-500nm), the red light band (600-700nm), and the near-infrared light band (700-780nm). This study utilizes the characteristic of plants absorbing blue and red light during photosynthesis, adjusting the spectrum to combine the strong blue light emission of glass ceramics with the supplementation of red light, thus fabricating a plant lighting device with the potential application in the field of plant lighting.
[0060] In summary, this invention prepares an Eu-doped material using an in-situ crystallization method of precursor glass under normal pressure. 2+ Rare earth ion-based glass-ceramic materials, prepared by controlling the component ratio, exhibit excellent physicochemical stability, superior thermal stability, and good luminescence performance. The preparation method provided by this invention is simple, low-cost, non-toxic, and pollution-free. The resulting glass-ceramic material possesses excellent luminescence properties and can be developed as a blue fluorescent solid-state luminescent material for laser lighting. By utilizing strong blue light emission and filling the red light band, it holds promise for applications in plant lighting.
[0061] The embodiments of the present invention have been described in detail above with reference to the accompanying drawings. However, the present invention is not limited to the above embodiments, and various changes can be made within the scope of knowledge possessed by those skilled in the art without departing from the spirit of the present invention. Furthermore, the embodiments of the present invention and the features thereof can be combined with each other unless otherwise specified.
Claims
1. A glass-ceramic, characterized in that, The glass-ceramic comprises the chemical formula BaMg2Al6Si9O 30 :xEu 2+ The crystal phase structure; and the value of x ranges from 0.1 to 0.9%.
2. The glass-ceramic according to claim 1, characterized in that, The glass-ceramic exhibits photoluminescence.
3. The glass-ceramic according to claim 2, characterized in that, The excitation spectrum of the glass-ceramic is in the range of 230~440nm; and / or, the peak of the emission spectrum of the glass-ceramic is in the range of 445~470nm.
4. The glass-ceramic according to claim 2 or 3, characterized in that, The photoluminescence quantum efficiency of the glass-ceramic is ≥43%; and / or, the ratio of the luminescence intensity of the glass-ceramic at 420K to 300K is ≥90%.
5. A method for preparing a glass-ceramic as described in any one of claims 1 to 4, characterized in that, The preparation method includes the following steps: S1. Mix magnesium source, aluminum source, silicon source, barium source and europium source, and melt and cool the resulting mixture in a reducing atmosphere; S2. The product obtained in step S1 is subjected to heat treatment in a reducing atmosphere; the temperature of the heat treatment is >950°C and <1100°C.
6. The preparation method according to claim 5, characterized in that, In step S1, the melting temperature is 1400~1500℃; and / or, in step S1, the melting time is 3~4h.
7. The preparation method according to claim 5, characterized in that, In step S2, the heat treatment lasts for 6 to 11 hours.
8. The preparation method according to claim 5, characterized in that, In step S1 and / or step S2, the reducing atmosphere is provided independently by at least one of carbon powder and hydrogen.
9. The preparation method according to claim 5, characterized in that, In step S1, the mixture comprises, by mole percentage: Magnesium source 18% ± 0.1%; Aluminum source 22% ± 0.1%; Silicon source 55% ± 0.1%; Barium source 5%±0.1%-x / 2; Europium source x / 2.
10. The application of a glass ceramic as described in any one of claims 1 to 4, or a glass ceramic prepared by any one of claims 5 to 9, in the field of lighting.